Analysis of Strain Partitioning in Intercritically Deformed Microstructures via Interrupted Tensile Tests - Unai Mayo; Nerea Isasti; José M. Rodríguez-Ibabe; Pello Uranga (Metals, 2021)
Intercritically deformed steels present combinations of different types of ferrite, such as deformed ferrite (DF) and non-deformed ferrite (NDF) grains, which are transformed during the final deformation passes and final cooling step. Recently, a grain identification and correlation technique based on EBSD has been employed together with a discretization methodology, enabling a distinction to be drawn between different ferrite populations (NDF and DF grains). This paper presents a combination of interrupted tensile tests with crystallographic characterization performed by means of Electron Backscatter Diffraction (EBSD), by analyzing the evolution of an intercritically deformed micro-alloyed steel. In addition to this, and using the nanoindentation technique, both ferrite families were characterized micromechanically and the nanohardness was quantified for each population. NDF grains are softer than DF ones, which is related to the presence of a lower fraction of low-angle grain boundaries. The interrupted tensile tests show the different behavior of low- and high-angle grain boundary evolution as well as the strain partitioning in each ferrite family. NDF population accommodates most of the deformation at initial strain intervals, since strain reaches 10%. For higher strains, NDF and DF grains behave similarly to the strain applied.